The Nones: where they came from, who they are, and where they are going - Burge, Ryan P. (ProQuest Ebook Central, 2021)
In The Nones: Where They Came From, Who They Are, and Where They Are Going, Ryan P. Burge details a comprehensive picture of Americans who say they have no religious affiliation. He gives readers a nuanced, accurate, and meaningful look at the growing number of Americans who say they have no religious affiliation. Burge explains how this rise happened, who the nones are, and what they mean for the future of American religion.